Lactobacillus murinus Improved the Bioavailability of Orally Administered Glycyrrhizic Acid in Rats - Yuan, Tianjie; Wang, Jin; Chen, Letian; Shan, Jinjun; Di, Liuqing (Frontiers in Microbiology, 2020)
Intestinal microbiota has been extensively studied in the context of host health benefit, and it has recently become clear that the gut microbiota influences drug pharmacokinetics and correspondingly efficacy. Intestinal microbiota dysbiosis is closely related with liver cirrhosis, especially the depletion of Lactobacillus. Therefore, the bioavailability of orally administered glycyrrhizic acid (GL) was speculated to be influenced under a pathological state. In the present study, L. murinus was isolated and screened for GL bioconversion capacity in vitro. Compared with Lactobacillus rhamnosus and Lactobacillus acidophilus, L. murinus was chosen for further investigation because it has the highest biotransformation rate. Our results showed that L. murinus could significantly improve the translocation of GL on Caco-2 cell models. Meanwhile, L. murinus was observed to have the ability to bind with the surface of Caco-2 cells and prominently downregulate the transporter gene expression level of multidrug resistance gene 1 (MDR1) and multidrug resistance protein 2 (MRP2), which were involved in the efflux of drugs. Furthermore, L. murinus was selected to be orally administred into rats in healthy and liver cirrhosis groups by a daily gavage protocol. Our data highlighted that supplements of L. murinus significantly improved the bioavailability of orally administered GL in rats, especially under a pathological condition, which may provide a novel strategy for improving the clinical therapeutic effect of liver protective drugs.